The Effectiveness of Sport Massage On Recovery In Athletes: Literature Review - Nur Alpiah, Dini; Putri Maharani, Aisya; Alya Syahda, Dinda; Wahyono, Eko (Worldwide Research Publishing, 2024)
Sports injuries are the most common problems experienced by athletes. Sports massage is non-invasive, easy to apply and does not cause side effects. The aim of this study was to determine the effectiveness of sports massage in athlete recovery. A literature review was carried out using PICO searches in several databases such as Google Scholar and Elshiver. Criteria were met in 6 reviews that reported sports massage performed 3 times a week for 4 weeks for 20 minutes with moderate pressure (2 cm depth). Of the several articles found, most used RCTs, quasi-experimental study designs and clinical trials with P<0.05. Both the experimental and control groups received sports massage. It can be concluded that sports massage is effective in speeding up the athlete's recovery process.